Fabricating TiO2 film with a facile spray-coating technique for dye-sensitized solar cells. (15th May 2016) - Song, Qingfeng; Zhu, Yajing; Zheng, Haikuo; Zhang, Fengbao; Wu, Mingxing
Abstract: Mesoporous TiO2 film is fabricated with simple spray-coating technique for dye-sensitized solar cells (DSCs) and the properties of this kind of TiO2 film are evaluated, compared to those prepared with conventional screen-printing and doctor-blading methods. Scanning electron microscope, N2 adsorption-desorption isotherms, and electrochemical impedance spectroscopy results demonstrate that the TiO2 film prepared with spray-coating method shows high porosity, large BET surface area, and fast charge transfer rate, indicating this method is suitable for preparing mesoporous TiO2 films. The power conversion efficiency of the rigid DSCs using spray-coating method is up to 7.1%, higher than those using screen-printing and doctor-blading techniques (6.6% and 6.2%). In addition, the spray-coating method is special for fabricating large scaled (2.7 cm 2 ) flexible DSCs in low temperature, and an efficiency of 2.4% is achieved. Graphical abstract: Highlights: The TiO2 film prepared with spray-coating method shows high porosity, large surface area, and fast charge transfer rate. The efficiency of the device using spray-coating method is higher than that using screen-printing or doctor-blading method. The spray-coating method is also special to fabricate large scaled flexible DSCs in low temperature.